Radiotracers Used for the Scintigraphic Detection of Infection and Inflammation - Chris Tsopelas (The Scientific World Journal)
Over the last forty years, a small group of commercial radiopharmaceuticals have found their way into routine medical use, for the diagnostic imaging of patients with infection or inflammation. These molecular radiotracers usually participate in the immune response to an antigen, by tagging leukocytes or other molecules/cells that are endogenous to the process. Currently there is an advancing effort by researchers in the preclinical domain to design and develop new agents for this application. This review discusses radiopharmaceuticals used in the nuclear medicine clinic today, as well as those potential radiotracers that exploit an organism’s defence mechanisms to an infectious or inflammatory event.